2022
DOI: 10.4102/hsag.v27i0.1937
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent paediatric transplant patients’ experiences of transition to adult services

Abstract: Background: Transition of adolescents from paediatric to adult health services is an important aspect of caring for young people with chronic diseases. Successful transition of adolescents living with a transplant is critical for long-term survival into adulthood. This qualitative study explored the lived experience of adolescents in a South African setting following their planned and supported transition process.Aim: To explore the lived experience of transition for adolescents who had received a renal or liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Most centres lack a formal transition programme from paediatric to adult care at the time of puberty, which may make these discussions particularly difficult. [19,20] Adolescent female patients may be faced with a new and unfamiliar healthcare team and a system less equipped to manage the complex care of adolescent patients (aged 10 -19 years). [21] Adolescence is a high-risk period for graft rejection; one SA study demonstrated a graft failure rate of 74.5% in adolescent renal transplant patients, although the majority (62.2%) occurred in male patients.…”
Section: Fertility Issuesmentioning
confidence: 99%
“…Most centres lack a formal transition programme from paediatric to adult care at the time of puberty, which may make these discussions particularly difficult. [19,20] Adolescent female patients may be faced with a new and unfamiliar healthcare team and a system less equipped to manage the complex care of adolescent patients (aged 10 -19 years). [21] Adolescence is a high-risk period for graft rejection; one SA study demonstrated a graft failure rate of 74.5% in adolescent renal transplant patients, although the majority (62.2%) occurred in male patients.…”
Section: Fertility Issuesmentioning
confidence: 99%